38 THE PREVALENCE OF POLYPHARMACY IN A SOUTHERN METROPOLITAN UNIVERSITY BASED AMBULATORY CARE CLINIC. (10th December 2015) - Vital, C. J.; Bhatnagar, D.; Kamboj, S.; Leierer, S.; McLean, A.; Borne, D.; Daberkow, D.; Fontenot, C.; Kumar, P.
Abstract : Polypharmacy, defined as consumption of 5 or more medications on a long term basis, has become increasingly prevalent, especially in the elderly population. Medications include prescription and over-the-counter medications as well as vitamins and herbal supplements taken on a weekly or daily basis. The charts of patients attending a large urban clinic in a metropolitan area in the southeast U.S. were reviewed to identify the prevalence of polypharmacy. Out of the 1123 charts of patients age 65 or over, 320 charts (107 male, 212 female) were randomly selected and considered eligible for the study. Fifty-one percent of the patients were African-American, 40% were Caucasian. Only those medical records that occurred within a one-year period from the date of the last clinic visit were used to gather the following information: patient's demographics, medical history, and medication record. Complete information was obtained on 290 patients and used in the statistical analysis of the data. Forty-nine percent of our patient population was on polypharmacy. Significant predictors of polypharmacy included the number of diagnoses, such as hypertension and diabetes, and patient gender. Women took significantly more pills than men (F = 17.217, p < .0005, women = 6.03, men = 4.74). As this pilot study shows, polypharmacy is common among seniors. Our findings suggest that further studies should be conducted to determine the predictors of polypharmacy in a geriatric population. Likewise, future intervention studies are needed to reduce inappropriate medication use, allowing a decrease in likeliness of adverse drug events and lowering health care costs.